Technical guidelines for the management of field and in vitro germplasm collections - Reed, B.M.; Engelmann, F.; Dulloo, Mohammad Ehsan; Engels, J.M.M.; International Plant Genetic Resources Institute (2004)
Plant species that are vegetatively propagated, that have long life cycles and/or produce nonorthodox seeds are traditionally maintained in field collections. Maintaining plants in the field is costly and carries high risks of loss; therefore, the strategies and procedures employed to establish and maintain field collections need to be practical, rational and economic, in addition to being scientifically sound. Experience in cost-effective management of field collections lies with individual curators and is not readily available to guide others. Further, there are increasing opportunities for using in vitro methods for the conservation of crops normally conserved in the field, and there is a need to develop strategies and procedures for managing in vitro collections as routine and integral part of the overall conservation strategy of a crop or collection.